Trade Reforms, Market Access, and Poverty in Argentina - Porto, Guido G. (World Bank, Washington, DC, 2014)
Much of the literature that studies the relationship between trade and poverty in developing countries focuses on the effects of national trade reforms, such as own tariff reductions. In contrast, the World Trade Organization negotiations at the Doha Round were more concerned with the poverty effects on low-income countries, and of foreign reforms, such as the elimination of agricultural subsidies in industrial economies. The author empirically compares the relative poverty impacts of national and foreign trade reforms in Argentina. The author investigates national trade reforms, including tariff cuts on consumption goods and capital goods in Argentina. Foreign trade reforms include the elimination, in industrial countries, of agricultural subsidies and trade barriers on agricultural manufactures and industrial manufactures. These policies enhance the market access of Argentine exports. Overall, a combination of own reforms and enhanced market access would cause poverty to decline by between 1.7 and 4.6 percentage points. This evidence suggests that trade policies can be important poverty-reducing instruments in Argentina.